Geographic Information System-Based Recommendations For Analyzing The Distribution Of Critical Land In The Citanduy River Basin Using The Modified SWAT Method - Suharsono, Teguh Nurhadi; Rosdiana, Rama; Mardiati, Rina (International Conference on Wireless and Telematics (Online), 2024)
A watershed is a geographical area through which a river and its tributaries flow, forming an interconnected network. It serves as a collection point for rainwater and other sources of water, which then flow through the tributaries and main river. The watersheds in most regions of Indonesia experience a significant strain because to the combination of a dense population and ongoing exploitation of natural resources. The escalating occurrence of landslides, the accelerating rate of soil erosion and sedimentation, as well as the occurrence of floods and droughts in various places, are indications of the deteriorating state of the watershed. The study employs an adapted SWAT (Soil and Water Assessment Tool) approach to effectively address many issues in the Citanduy watershed, with a particular focus on analyzing crucial land-related challenges. The utilization of GIS for mapping the distribution of crucial land in the Citanduy watershed has not been extensive. This study intends to assess the criticality of the Citanduy watershed in achieving sustainable watershed management through mapping. The final outcome of each map is overlaid to accurately determine the extent of crucial land and create a standardized map that may serve as a reference for the government in policy-making. The research findings indicate that 50.01% of the land, covering an area of 1820.484 Km2, experienced a high rate of land erosion. Additionally, 48.71% of the land, spanning 1773.14 Km2, had a medium land erosion rate. The remaining 1.28% of the land, which covered an area of 46.61 Km2, had a low land erosion rate. The average land erosion in the Citanduy River Basin is 160,566 tons per hectare per year.